A secreted-Cu/Zn superoxide dismutase from Microplitis bicoloratus reduces reactive oxygen species triggered by symbiotic bracovirus. (March 2019) - Zhang, Li-Dan; Cai, Qiu-Cheng; Cui, Ji-Hui; Zhang, Wei; Dong, Shu-Mei; Xiao, Wei; Li, Jiang; Kou, Tian-Chao; Zhang, Xue-Wen; He, Hao-Juan; Ding, Lei; Yang, Yang; et al.
Abstract: In the parasitoid/polydnavirus/host system, polydnaviruses protect larva development in the host hemocoel by suppressing the host immune response. However, the negative effects on the parasitoid and the strategy of the parasitoid to deal with this disadvantage are still unknown. Microplitis bicoloratus bracovirus induces granulocyte apoptosis to suppress immune responses, resulting in an apoptotic haemolymph environment in which immature M. bicoloratus larva develop. Here, we determined the transcriptional profiles of immature M. bicoloratus across five time-points throughout the immature developmental process from egg to third instar. Dynamic gene expression pattern analysis revealed clear rapid changes in gene expression characteristic of each developmental stage, indicating faster sequential unambiguous functional division during development. Combined with the proteome of the host haemolymph, immature parasitoids likely secreted a Cu/Zn superoxide dismutase to reduce reactive oxygen species generation by symbiotic bracovirus. These data established a basis for further studies of parasitoid/host interactions and identified a novel positive self-protection mechanism for the parasitoid. Highlights: Immature parasitoids secreted a Cu/ZnSOD. Cu/ZnSOD reduces ROS triggered by bracovirus. A positive self-protection mechanism.